Pediatric appendicitis: Is referral to a regional pediatric center necessary?. Issue 4 (April 2018) - Hodges, Maggie M.; Burlew, Clay Cothren; Acker, Shannon N.; Moore, Ernest E.; Roosevelt, Genie E.; Schubert, Anna; Hill, Lauren R.S.; Partrick, David A.; Bensard, Denis
Abstract : BACKGROUND: Acute appendicitis is the most common emergent surgical procedure performed among children in the United States, with an incidence exceeding 80, 000 cases per year. Appendectomies are often performed by both pediatric surgeons and adult general/trauma and acute care (TACS) surgeons. We hypothesized that children undergoing appendectomy for acute appendicitis have equivalent outcomes whether a pediatric surgeon or a TACS surgeon performs the operation. METHODS: A retrospective chart review was performed for patients 6 to 18 years of age, who underwent appendectomy at either a regional children's hospital (Children's Hospital of Colorado [CHCO], n = 241) or an urban safety-net hospital (n = 347) between July 2010 and June 2015. The population of patients operated on at the urban safety-net hospital was further subdivided into those operated on by pediatric surgeons (Denver Health Medical Center [DHMC] pediatric surgeons, n = 68) and those operated on by adult TACS surgeons (DHMC TACS, n = 279). Baseline characteristics and operative outcomes were compared between these patient populations utilizing one-way analysis of variance and χ 2 test for independence. RESULTS: When comparing the CHCO and DHMC TACS groups, there were no differences in the proportion of patients with perforated appendicitis, operative time, rate of operative complications, rate of postoperative infectious complications, or rate of 30-day readmission. Length of stay was significantly shorter for the DHMC TACS group than that for the CHCO group. CONCLUSIONS: Our data demonstrate that among children older than 5 years undergoing appendectomy, length of stay, risk of infectious complications, and risk of readmission do not differ regardless of whether they are operated on by pediatric surgeons or adult TACS surgeons, suggesting resources currently consumed by transferring children to hospitals with access to pediatric surgeons could be allocated elsewhere. LEVEL OF EVIDENCE: Therapeutic/Care management, level III.